Political and Social Compacts for Equality and Sustainable Development in Latin America and the Caribbean in the Post-COVID-19 Recovery - Economic Commission for Latin America; the Caribbean (United Nations, 2020)
The coronavirus disease 2019 (COVID-19) pandemic hit Latin America and the Caribbean in a period of economic, social and environmental vulnerability. Tackling the health crisis —which has outlasted initial forecasts— and its deleterious economic and social effects will require political and social compacts built on broad multi-stakeholder participation that universalize social protection and health and, above all, refocus development on equality and on fiscal, production and environmental policies for sustainability. Compacts must be directed towards laying the foundations for a welfare state that, among other things, ensures universal access to health, redistributive taxes, increased productivity, better provision of public goods and services, sustainable management of natural resources and more substantial and diversified public and private investment.